Aspects of the ecology and conservation status of selected wildlife in and around Tembe Elephant Park, KwaZulu-Natal, South Africa - Bothma, Jacobus du P. (University of Pretoria, 2013)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 2007.